MOTIVASI ORANG TUA MENYEKOLAHKAN ANAK KE PONDOK PESANTREN (Studi Kasus : 5 Orang Tua yang Anaknya Bersekolah di Pondok Pesantren Dar El Hikmah Pekanbaru) - Robbi Andhika Aprianto Aprianto; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study analyzes the motivation of parents schooling their children to Islamic boarding schools conducted at Dar El Hikmah Boarding School in Panam, Pekanbaru. By using qualitative methods with a purposive sampling technique to assign informants, the authors assign 5 informants to explain what motivates parents schooling their children to boarding schools. The results of this study found that the motivation of parents schooling their children to the Dar El Hikmah Panam Islamic Boarding School in Pekanbaru included two types of motivation, namely intrinsic motivation and extrinsic motivation. Intrinsic motivation is a motivation which comes from themselves. Meanwhile, extrinsic motivation is a motivation which obtains from the neighbourhood, and others. Some informants whom the authors met also explained that their motivation schooling their children to Islamic boarding schools was because of the environment where they lived. Most children went to Dar El Hikmah Islamic Boarding School, and also there was encouragement from families who thought that there were many benefits to be gained if children went to Islamic boarding school. By studying at Islamic Boarding School, the parent expects that their children become a good person. Not only good at academic achievement but also have good behaviour and personalities. Every parent expects for the best future for their children and also wants to have successful children so that there is something to be proud of by them.               Keywords: Motivation, Parents, Boarding school